2006
DOI: 10.1021/ja063063b
|View full text |Cite
|
Sign up to set email alerts
|

Highly Selective Room-Temperature Copper-Catalyzed C−N Coupling Reactions

Abstract: Through the use of cyclic beta-diketones as supporting ligands, the copper-catalyzed coupling of aryl iodides with aliphatic amines occurs at room temperature in as little as 1 h. These high reaction rates allow for the coupling of a wide range of aryl and heteroaryl iodides at room temperature. This method is highly tolerant of a number of reactive functional groups, including -Br and aromatic -NH2 as well as phenolic and aliphatic -OH. The high selectivity of the CuI-beta-diketone catalyst for aliphatic amin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
193
0
8

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 415 publications
(205 citation statements)
references
References 9 publications
(8 reference statements)
2
193
0
8
Order By: Relevance
“…For the 4-hexyloxyphenyl-substituted phenoxazines, MP12 and MP05, the initial arylation to give 7 followed a procedure reported by Buchwald and coworkers. [52,53] Formylation of 1 and 7 was accomplished by the Vilsmeyer-Haack reaction. Higher yields of 4 and 8 were obtained by heating the reaction mixture to reflux in CHCl 3 overnight, compared to heating in pure dimethylformamide (DMF).…”
Section: Methodsmentioning
confidence: 99%
“…For the 4-hexyloxyphenyl-substituted phenoxazines, MP12 and MP05, the initial arylation to give 7 followed a procedure reported by Buchwald and coworkers. [52,53] Formylation of 1 and 7 was accomplished by the Vilsmeyer-Haack reaction. Higher yields of 4 and 8 were obtained by heating the reaction mixture to reflux in CHCl 3 overnight, compared to heating in pure dimethylformamide (DMF).…”
Section: Methodsmentioning
confidence: 99%
“…[5][6][7][8][13][14][15][16] Warren's group 8 has isolated a Ni( -diketiminate)nitrene complex that can effect C-H activation of 1,4-cyclohexadiene (CD-H). Amination by late metal catalysts (notably Pd 17 and Cu 18 ) is established in organic synthesis but involves initial functionalization of a hydrocarbon to produce a more reactive surrogate (e.g., organic chloride). Direct amination of hydrocarbons is more desirable from an atomeconomical viewpoint.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is desirable to develop milder copper-catalyzed coupling methods. Recently, Shafir and Buchwald [9] and ourselves [10] have developed copper-catalyzed N-arylations at room temperature, and the results showed that the efficiency of the copper-catalyzed coupling reactions was highly dependent on the involvement of suitable ligands. To the best of our knowledge, there is no example of constructing N-heterocycles under ligand-free copper catalysis at room temperature.…”
mentioning
confidence: 99%